Effect of benzylamino purine and naphtahaleneacetic acid on shoot proliferation and growth In vitro of Coffea arabica L. - Pasqual, Moacir; de Barros, Inacio (Pesquisa Agropecuaria Brasileira, 1991)
Tissue culture technique is an important instrument for genetic plant breeding and plant propagation. Shoots with nearly 3 mm, excised from seedlings obtained in vitro of Coffea arabica L. Cv. catuaí, line LC-2077-2-5-44, were inoculated on medium composed of salts of Murashige and Skoog, vitamins of Morel, myoinositol (100 mg.l-1), glycine (2 g.l-1), sucrose (30 g.1-1) and agar (7 g.1-1), additioned by benzylamino purine (BAP) (0, 500, 1.000, 2.000, 2.500, 3.000, 3.500 and 4.000 mg.l-1) and naphthaleneacetic acid (NAA) (0 and 200 mg.l-1). The experiment was carried out under light (16 hours photoperiod) and 27oC. The total bud multiplication was best on the medium with BAP 3.000 mg.l-1 without NAA, after 90 days of culture. The best proliferation of shoots bigger than 1 cm took place in BAP 500 mg.l-1 concentrations. The use of NAA 200 mg.l-1 caused damage to shoot proliferation.